The evolution of Islamic theological discourse in the classical era: A Historical-linguistic perspective - Rahman, Hafiz Mahmood (Journal of Religion and Linguistics, 2025)
This work contests the prevailing historiographical belief that political struggle was the principal catalyst for the evolution of classical Islamic theology (‘ilm al-kalām).  This study contends that, although political events offered context, the primary causative cause was the diversity in interpretive procedures, particularly the differing linguistic approaches to the Quranic text.  The prevalent notion that early scholars (ulama mutaqaddimin) adhered strictly to literary literalism is disputed; evidence indicates that many utilized advanced rational, context-sensitive, and semantically complex interpretations.  This article conducts a historical-linguistic examination of how classical theologians interacted with divine discourse through the use of analogy, metaphor, and semantic differentiation.  These linguistic methods were not only rhetorical but also fundamental to essential theological ideas like divine characteristics, human agency, and sin.  The establishment of the Mu'tazilah, Ash'ariyyah, and Maturidiyyah schools illustrates the formation of doctrinal identity through language, while discussions surrounding terminology like as īmān (faith), kufr (disbelief), and qadar (divine decree) reveal significant semantic conflicts within early Islamic discourse.  This study emphasizes linguistic hermeneutics, revealing the underlying discursive dynamics that diversified Islamic thought and demonstrating that classical theology was shaped equally by philological engagement and philosophical or political contestation.